(untitled) (Journal of Informatics Education and Research, 2025)
Gender Equality and Social Inclusion are crucial for achieving social transformation, particularly in developing regions where gender roles are deeply rooted. This study examines the impact of Facilitation for Empowerment and Social Transformation(FEST) approach in multidimensional empowerment of marginalized groups in the Dang and Jajarkot districts of Nepal. These districts, having many socio-economic challenges, are representative of rural Nepal where gender and social discrimination are can be widely seen. The study tries to explore how FEST approach and its process have contributed to enhancing women’s and marginalized groups status in the rural society. A mixed method survey was conducted in two districts of Nepal. Quantitative data was analyzed for 324 members of different community groups from both the control and non-control groups. Key informant interviews were conducted among community group members, including collections of some case studies are done for qualitative data.